75-mm wingspan fixed-wing nano air vehicle with a novel aircraft configuration - Pushpangathan, Jinraj V. (2019)
The development of a fixed-wing nano air vehicle that fits inside a cube of 75 mm is described in this paper. A novel aircraft configuration that satisfies the static and dynamic stability and the mission performance requirements is developed. A performance index is formulated to identify a suitable airfoil as there does not exist a single airfoil that achieves the mission required specifications. Eppler-61 is identified as the suitable airfoil since the value of its performance index is maximum among other airfoils selected for the analysis. The static stability of the nano air vehicle is analyzed using the aerodynamic characteristics obtained from the wind tunnel tests. The outcomes of this analysis indicate that the vehicle is statically stable. The analysis also indicates significant aerodynamic cross-coupling between longitudinal and lateral aerodynamic coefficients. The dynamic stability analysis indicates that the nano air vehicle is dynamically stable. Furthermore, the dynamic stability of the vehicle is validated by flight test results.